Islamic Fasting Models but not Only Ramadan Improved Metabolic Parameter in High-Fat-High-Fructose-Induced Rats - Ismail, Naufal Arif; Pramaningtyas, Miranti Dewi; Nurmasitoh, Titis (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Various types of Islamic fasting, apart from Ramadan fasting, have not been studied for their effects on health and metabolic processes. AIM: This study aimed to evaluate the effect of models of Ramadan, Dawood, and Monday-Thursday fasting on metabolic parameters in high-fat-high-fructose (HFHF)-induced rats. METHODS: Wistar rats were subjected to normal diet control, HFHF diet alone, and modeling Islamic fastings such as Ramadan, Dawood, and Monday-Thursday fasting models, within a period of 29 days at night that HFHF previously induced for 2 weeks. Serum lipid profile, glucose, uric acid, aspartate transaminase (AST) and alanine transaminase (ALT) for liver function, and urea and creatinine for kidney function were assessed after HFHF induction (pre-test) and after fasting treatment (post-test). RESULTS: HFHF administration for 2 weeks caused dyslipidemia and increased urea levels significantly. However, other parameters were impaired but not statistically significant. Islamic fasting models demonstrated a significantly improved lipid profile. However, glucose, uric acid, AST, ALT, urea, and creatinine improved after fasting treatment but were not statistically significant. CONCLUSION: Islamic fasting models have a beneficial effect on improving metabolic parameters. Both Dawood and Monday-Thursday fastings can be considered to promote health and improve metabolic processes as well as Ramadan fasting.